Perturbation Functions for Compact Database - Vyatkin, Sergey I (Review of Computer Engineering Research, 2017)
3D Objects based on perturbation functions are considered in this paper. For shape creating a set of algorithms and software based on function-defined surfaces that perform an interactive rate and enable intuitive operations was proposed. Interactive modification of the 3D objects allows us to provide high level of detail leading to a photo-realistic appearance of the resulting shapes.